IMPLICATIONS OF SARBANES-OXLEY ACT SECTION 404 TO THE EFFECTIVENESS OF INTERNAL CONTROL - Yayat Achdiat (Indonesian Management and Accounting Research, 2011)
Financial crisis in many countries in the world since 1990 and the mid-1997 that envolved into economic crisis. a crisis of trust, and multi-dimentional crisis, which could effect the fall of the country's leaders establish in the Indonesian, shows that the financial system has a very starteeic role in the economy. and has a significant correlation and positif with the economic system. This research 4nd that the internal control model based on the Sarbanes-Oxley Act section 404 has the advantage than control models in the current conducted. SOA section 404 advantage is the inclusion of management asersi and public accountant atest in financial report, which requires the integrity of corporate management and public accountants as external auditors, because the asersi and atest should be based on the documents submitted and the results of assessment on the audit and internal control implemention. Thus if the model Sarbanes-Oxley Act is implemented then presented the financial report accountability will be more accurate.